Foreign Direct Investment in India - A Case Study of Supermarkets, Hypermarkets, Superstores and Retail chains - Agarwal, Ashish (Journal of Commerce and Trade, 2012)
Henry Ford, the genius inventor and the owner of the world’s largest car company, once said, “Don’t find fault, find a remedy”. This saying echoes ever so relevantly in today’s Indian Retail Sector scenario like never before. India has been one of the most sought-after destinations for foreign investors across the globe. The Retail Sector in particular has been one of the sectors where there has been a constant buzz and excitement surrounding Government policy shaping the sector. The Indian Retail Sector has primarily comprised of Unorganized Players in the form of locally owned, Grocery Shops (kirana stores), Road side Wooden Structures (paan khokha/shops), Multipurpose Stores (general stores), Hand Cart (redi-wala) and Pavement Vendors (footpath penth), etc. On the other hand, Organized Retailing involves trading activities undertaken by licensed retailers, that is, those who are registered for Sales Tax and Income Tax. The corporate-backed Super Markets, Hyper Markets and Retail Chains and the privately owned large retail businesses are also present in India. However, the tremendous growth prospect of the sector coupled with successfully established models of organized retail in other Asian markets such as China has paved the way for the establishment of organized retail in India as well. In addition to this, a number of home-grown corporate giants such as Future Group and Aditya Birla Group have furthered the cause of organized retail by setting up exclusive outlets across India.